Optimisation of a sampling protocol for long-term monitoring of temperate reef fishes - Bennett, Rhett Hamilton (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2008)
Marine Protected Areas (MPAs), the Ecosystem Approach to Fisheries management (EAF) and Integrated Coastal Management (ICM) have been identified as possible alternatives to traditional linefish management measures, which have largely failed. Monitoring and assessment of fish communities on a long-term basis is necessary, and will provide a means to evaluate the effectiveness of such management measures. Therefore, standardised protocols and optimal sampling methods for long-term monitoring (LTM) and assessment of coastal fish communities are essential. This study aimed to identify suitable methods and develop a protocol for assessment of inshore reef fish communities. A suitable location for evaluation of proposed methods was identified in the warm temperate biogeographical region of South Africa, encompassing the well-established Tsitsikamma Coastal National Park MPA and an adjacent exploited area. Chrysoblephus laticeps (roman) was identified as an indicator species for the study, as it has been well-studied and is well represented in the area. Underwater visual census (UVC) and controlled fishing were identified as suitable methods. UVC transects were found to be superior to point counts, in terms of sampling efficiency, variability, bias and required sample size. An effort of two angler hours per fishing station was shown to provide low catch variability, while at the same time a representative catch and low overall cost and required time. The methods were incorporated in a proposed sampling protocol, and evaluated. The methods were able to detect known differences between protected and exploited communities. It is recommended that LTM within protected areas, for detection of natural change, be focused on community-level indicators, while LTM in exploited areas, aimed at detection of anthropogenic change, be focused on species-level indicators. The proposed protocol with standardised methods will allow for comparisons across a network of LTM sites and provide the opportunity for a broad-scale assessment of the effects of environmental variables on reef fish stocks. The protocol developed in this study has application in other biogeographical regions in South Africa, and other parts of the world. Shift in the focus of much marine research, in South Africa and elsewhere, to LTM, highlights the relevance and timeous nature of this study.
Keywords: Marine parks and reserves -- South Africa; Coastal zone management -- South Africa; Fishery management -- South Africa; Reef fishes -- South Africa; Fish communities -- South Africa; Fish stock assessment